Pengenalan Kearifan Lokal di Majalengka dengan Media Video Game Menggunakan Unity Engine - Nugraha, Algi; Bastian, Ade (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Indonesia is rich in cultural heritage, yet modernization has caused younger generations to show greater interest in foreign cultures rather than local traditions. This issue highlights the need for innovative approaches to preserve and promote local wisdom. This study aims to introduce Majalengka’s local culture through the development of an interactive video game “PENA: Desa Terlarang.” The research employed the Game Development Life Cycle (GDLC) method, consisting of initiation, pre-production, production, testing, beta, and release stages. Data were collected through field research at the Majalengka Creative Center (MCC) and literature studies to integrate cultural values into the game’s narrative and design. The resulting game adopts an adventure-horror genre with puzzle elements, allowing players to explore traditional stories, interact with cultural artifacts, and solve challenges inspired by local myths. Technical implementation was carried out using Unity Engine and Blender for modeling, supported by design patterns such as Finite State Machine, Observer, and Singleton to manage game logic and events. The findings show that the game not only provides entertainment but also effectively educates players about local culture while enhancing reasoning skills through gameplay. This research demonstrates that video games can serve as a creative and engaging medium for cultural preservation.